Indonesian Tourism Demand Forecasting using Time Series Approach to Support Decision Making Process - Putu Bella Ayastri Friscintia (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2019)
Tourism industry is always growing dan uphold an important role in national economy as the second largest portion of foreign exchange contributor, as well as its role in national employment. In improving tourism industry, forecasting is needed to anticipate the perishable nature of tourism. Therefore, an accurate forecasting is needed as the baseline of strategic resource planning in order to maximize the utilization dan efficiency of the available resources. The objective of this research is to build an accurate model that is able to forecast Indonesian tourism demand. This research use ARIMA algorithm to forecast the arrivals of tourist. The result of this paper is a time-series model for tourist arrivals in Indonesia Keywords: Tourism, Demand Forecasting, ARIMA, Indonesia.